Examining the structure-activity relationship of benzopyran-based inhibitors of the hypoxia inducible factor-1 pathway. Issue 8 (15th April 2017) - Ferguson, Jalisa; De Los Santos, Zeus; Devi, Narra; Van Meir, Erwin; Zingales, Sarah; Wang, Binghe
Graphical abstract: Abstract: Many forms of solid tumor have a characteristic feature known as hypoxia, which describes a low or non-existent presence of oxygen in the cellular microenvironment. This decrease in oxygen causes activation of the hypoxia inducible factor (HIF) pathway, which activates the transcription of many genes that cause cell proliferation, metastasis, increased glycolysis and angiogenesis. Increased HIF expression has been linked with poor patient prognosis, increased malignancy, and therapeutic resistance. Previous work in our lab has identified1 and2 as inhibitors of the HIF pathway, specifically as disrupters of the p300-HIF-1α complex formation. A library of sulfonamide analogs has been designed and synthesized with the intent of examining the SAR of this series of compounds and improving potency and physicochemical properties as compared with lead compounds1 and2 . At the end, we have achieved a thorough understanding of the structural features critical for future optimization work.